A novel sensor-embedded holding device for monitoring upper extremity functions - Ma, Charlie Chen; Mo, Pu-Chun; Hsu, Hsiu-Yun; Su, Fong-Chin (Frontiers in Bioengineering and Biotechnology, 2022)
There are several causes that can lead to functional weakness in the hands or upper extremities (UE), such as stroke, trauma, or aging. Therefore, evaluation and monitoring of UE rehabilitation have become essential. However, most traditional evaluation tools (TETs) and assessments require clinicians to assist or are limited to specific clinical settings. Several novel assessments might apply to wearable devices, yet those devices will still need clinicians or caretakers to help with further tests. Thus, a novel UE assessment device that is user-friendly and requires minimal assistance would be needed. The cylindrical grasp is one of the common UE movements performed in daily life. Therefore, a cylindrical sensor-embedded holding device (SEHD) for training and monitoring was developed for a usability test within this research. The SEHD has 14 force sensors with an array designed to fit holding positions and a six-axis inertial measurement unit (IMU) to monitor grip strength, hand dexterity, acceleration, and angular velocity. Six young adults, six healthy elderly participants, and three stroke survivors had participated in this study to see if the SEHD could be used as a reference to TETs. During result analyses, where the correlation coefficient analyses were applied, forearm rotation smoothness and the Purdue Pegboard Test (PPT) showed a moderate negative correlation [r (16) = −0.724, p < 0.01], and the finger independence showed a moderate negative correlation with the PPT [r (10) = −0.615, p < 0.05]. There was also a highly positive correlation between the maximum pressing task and Jamar dynamometer in maximum grip strength [r (16) = 0.821, p < 0.01]. These outcomes suggest that the SEHD with simple movements could be applied as a reference for users to monitor their UE ability.